Conflicting Uses of Metaphors: Reconceptualizing Their Use in the Field of Organizational Change - Palmer, Ian; Dunford, Richard (Academy of Management Review, 1996)
Diverse and often unacknowledged assumptions underlie the use of metaphors in the organizational change literature. This diversity is symptomatic of broader ontological and epistemological conflicts within organization theory. To gain a critical awareness of the assumptions underlying their use of metaphors, organizational analysts can use a reflexive approach. This approach entails addressing four issues: representation, enunciation, separation, and routinization. The organizational change literature is used to illustrate the implications of this approach for future research.